Interactions Between Neutrophils and Periodontal Pathogens in Late-Onset Periodontitis - Jiang, Qingsong; Zhao, Yuxi; Shui, Yusen; Zhou, Xuedong; Cheng, Lei; Ren, Biao; Chen, Zhu; Li, Mingyun (Frontiers in Cellular and Infection Microbiology, 2021)
Late-onset periodontitis is associated with a series of inflammatory reactions induced by periodontal pathogens, such as Porphyromonas gingivalis, a keystone pathogen involved in periodontitis. Neutrophils are the most abundant leukocytes in the periodontal pocket/gingival crevice and inflamed periodontal tissues. They form a “wall” between the dental plaque and the junctional epithelium, preventing microbial invasion. The balance between neutrophils and the microbial community is essential to periodontal homeostasis. Excessive activation of neutrophils in response to periodontal pathogens can induce tissue damage and lead to periodontitis persistence. Therefore, illuminating the interactions between neutrophils and periodontal pathogens is critical for progress in the field of periodontitis. The present review aimed to summarize the interactions between neutrophils and periodontal pathogens in late-onset periodontitis, including neutrophil recruitment, neutrophil mechanisms to clear the pathogens, and pathogen strategies to evade neutrophil-mediated elimination of bacteria. The recruitment is a multi-step process, including tethering and rolling, adhesion, crawling, and transmigration. Neutrophils clear the pathogens mainly by phagocytosis, respiratory burst responses, degranulation, and neutrophil extracellular trap (NET) formation. The mechanisms that pathogens activate to evade neutrophil-mediated killing include impairing neutrophil recruitment, preventing phagocytosis, uncoupling killing from inflammation, and resistance to ROS, degranulation products, and NETs.